Chemical reactions of organic compounds in supercritical water gasification and oxidation. (15th February 2021) - Wei, Ning; Xu, Donghai; Hao, Botian; Guo, Shuwei; Guo, Yang; Wang, Shuzhong
Highlights: · Chemical reactions of different organics in supercritical water are summarized. · Intermediate and final products above are discussed comprehensively. · Reaction processes of organics with the same functional group are deeply compared. · Bond fracture characteristics of reactants are described in detail. · Supercritical water treatment prospects are systematically analyzed. Abstract: Supercritical water is a benign reaction medium to convert organic matters through supercritical water gasification and supercritical water oxidation into flammable gaseous and harmless substances, respectively. This work systematically summarizes main chemical reactions of some typical organic compounds in supercritical water with or without oxidant for the first time. These compounds include hydrocarbons, proteins, cellulose, lignins, phenols, alcohols, aldehydes, ketones, organic acids, and some N-, Cl-, Br-, F-, S- and P-containing organic matters. Their main conversion pathways, reaction processes, intermediate products, final products and influence factors are analyzed deeply. This information helps to understand and predict corresponding reaction mechanisms and to better achieve objective products in supercritical water gasification and supercritical water oxidation. Graphical Abstract: Image, graphical abstract